2021
DOI: 10.1002/mabi.202100265
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilicate‐Functionalized Polycaprolactone Orchestrates Osteogenesis and Osteoblast‐Induced Multicellular Interactions for Potential Endogenous Vascularized Bone Regeneration

Abstract: Massive oral and maxillofacial bone defect regeneration remains a major clinical challenge due to the absence of functionalized bone grafts with ideal mechanical and proregeneration properties. In the present study, Laponite (LAP), a synthetic nanosilicate, is incorporated into polycaprolactone (PCL) to develop a biomaterial for bone regeneration. It is explored whether LAP-embedded PCL would accelerate bone regeneration by orchestrating osteoblasts to directly and indirectly induce bone regeneration processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…Therefore, the nano brous membrane with 5 wt% LAP incorporation in the present study was customized by electrospinning. Our results demonstrated PCL/LAP nano brous membrane possessed higher mechanical properties, which might contribute to the incorporation of LAP with a exfoliation status [17]. The PCL/LAP nano brous membrane had no adverse effects on PDLCs.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Therefore, the nano brous membrane with 5 wt% LAP incorporation in the present study was customized by electrospinning. Our results demonstrated PCL/LAP nano brous membrane possessed higher mechanical properties, which might contribute to the incorporation of LAP with a exfoliation status [17]. The PCL/LAP nano brous membrane had no adverse effects on PDLCs.…”
Section: Discussionmentioning
confidence: 67%
“…PCL is a widely used polymer with superior biocompatibility, and LAP is biocompatible and noncytotoxic within a suitable concentration range [11,14,15,26]. A series of nanosilicate-incorporated PCLs with different amounts of LAP particles were developed in our previous study [16,17], and we found that PCL with 5 wt% LAP had excellent biological properties. Therefore, the nano brous membrane with 5 wt% LAP incorporation in the present study was customized by electrospinning.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations